PENGEMBANGAN MEDIA GAMBAR “ MYSTERY BOX READ ” BERBASIS KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BACA TULIS SISWA DI SDN BEKTIHARJO VI DI KELAS 1 - Ervarisma Nur Aqqidahtul Izzah; Ina Agustin (Prodi PGSD Universitas PGRI Ronggolawe, 2024)
The achievements in the development of the research aim to describe the development of media, the level of validity, practicality of the media, and the effectiveness of the media. This study uses a type of research and development (R&D) research. The ADDIE development model has 5 stages in the ADDIE model, including: 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluate. Data collection instruments use observation sheets, interview sheets, and expert validation sheets. Subjects of the character-based